Optimalisasi Kenyamanan Ibadah Melalui Perancangan Interior Masjid Daarul Jannah Perumahan Palem 1 Residence Bandung - Nur Arief Hapsoro; Desthyo Putra Pangestu; Mohd Ridho Kurniawan; Melissa Celia; Salsabila Ruzika Maruwa; Muhammad Rifqy Adi Susilo (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Daarul Jannah Mosque, located in Palem 1 Adhyaksa Sukapura Complex, Bandung Regency, is the result of a local community initiative through self-help. In addition to being a place of worship, this mosque is also expected to function as a centre for community social activities. However, the results of observations and interviews with the Chairperson of the Mosque Prosperity Council (DKM) and the local RT Chairperson identified several problems with the interior elements of the mosque. These problems include the partition between the male and female prayer areas that is not optimal, the storage racks for prayer equipment that are not by needs, and the lack of ergonomic lesehan tables for religious study activities. In addition, the layout and function of the room are still not well organized, and there is no child-friendly space that can be used as an education centre. This community service aims to provide recommendations for more optimal interior design and arrangement according to the needs of the mosque and the local community. The methods used include location surveys, interviews with related parties, literature studies, and periodic design processes involving discussions between the service team and the mosque. The final result of this activity is a product of interior partition design for male and female prayer areas, recommendations for storage cabinet designs in the male and female areas, and a lesehan prayer table.